2013
DOI: 10.1371/journal.pone.0072855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Significance of Paleophylogeographic Species Distribution Models in Reconstructing Quaternary Range-Shifts of Nearctic Chelonians

Abstract: The climatic cycles of the Quaternary, during which global mean annual temperatures have regularly changed by 5–10°C, provide a special opportunity for studying the rate, magnitude, and effects of geographic responses to changing climates. During the Quaternary, high- and mid-latitude species were extirpated from regions that were covered by ice or otherwise became unsuitable, persisting in refugial retreats where the environment was compatible with their tolerances. In this study we combine modern geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 135 publications
4
72
1
Order By: Relevance
“…In the Cretaceous, the peak in both raw and subsampled generic richness was further north at 30–45° N (rather than 15–30° N as seen today [6]), and the raw data suggest that it may have shifted even further north to 45–60° N during the Maastrichtian although this peak is less pronounced in the subsampled data (figure 1 c ). These results are consistent with other studies that have demonstrated that LBGs are not constant through time, but are dynamic patterns that are strongly affected by changes in global climatic regimes [4,15]. They cannot be regarded as fixed global patterns for all taxa, contrary to widely held assumptions, nor can we expect future LBGs to necessarily retain a tropical to subtropical peak [4], within the climatic constraints imposed by the biological limitations of ectothermy and obligate ovipary [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the Cretaceous, the peak in both raw and subsampled generic richness was further north at 30–45° N (rather than 15–30° N as seen today [6]), and the raw data suggest that it may have shifted even further north to 45–60° N during the Maastrichtian although this peak is less pronounced in the subsampled data (figure 1 c ). These results are consistent with other studies that have demonstrated that LBGs are not constant through time, but are dynamic patterns that are strongly affected by changes in global climatic regimes [4,15]. They cannot be regarded as fixed global patterns for all taxa, contrary to widely held assumptions, nor can we expect future LBGs to necessarily retain a tropical to subtropical peak [4], within the climatic constraints imposed by the biological limitations of ectothermy and obligate ovipary [30].…”
Section: Discussionsupporting
confidence: 93%
“…This range expansion might have been driven by short-term continental scale temperature increases from the Early to Late Maastrichtian that enabled some turtles to increase their ranges [31,32]. The persistence of peak richness at mid-latitudes in the Northern Hemisphere throughout the Mesozoic, despite turtles having a wider latitudinal range than at present [18], and the evidence for a propensity for range expansion in response to climate change in both the Cretaceous [31] and more recent times [15], suggests that persistent abiotic mechanisms control these latitudinal patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend once again conspicuously mirrors global temperature estimates, which show stark cooling following the Early Eocene climatic optimum [66,67]. In contrast to the rise in disparity throughout the Mesozoic (where climate change might have played a subliminal role), we find a climatically controlled decrease in Tertiary disparity to be highly plausible (see the electronic supplementary material, S2, Text S3 and tables S20 and S22), as global cooling has otherwise been shown to have significant impact on the diversity of turtles, at least as demonstrated in North America where Palaeogene turtle faunas are well sampled and well understood [87][88][89]. As the principal mechanism, we suggest habitat loss resulting from the global drying that accompanied global cooling [90].…”
Section: Discussionmentioning
confidence: 99%
“…15) and interglacial warming periods and changes leading to landscape aridification and sea level changes have caused fluctuating distributions of many species and created refugia where speciation has occurred. Rödder et al (2013) modeled range extensions and contractions of 59 extant North American freshwater and semi-terrestrial turtle species through three Quaternary glacial and interglacial cycles from 320,000 ybp through the present. They found that although fossils of these species usually occurred within predicted thermal niches, based on extant populations of the same species, they sometimes occurred outside these niches, suggesting that the species' thermal niches might be much more flexible and less directly climate-dependent than previously assumed.…”
Section: Climate and Habitat Changementioning
confidence: 99%